Adhocracy Culture as Correlate of Teachers’ Service Delivery in Public Secondary Schools in Anambra State - Samuel Ogechukwu Otugo; Choice Chimaa Okaforcha (MANDAILING GLOBAL EDUKASIA, 2025)
Effective teachers’ service delivery is critical for achieving quality education, yet many public secondary schools in Anambra State face challenges of low teacher motivation, limited innovation, and poor instructional outcomes. These issues may be influenced by the prevailing organizational culture within schools. The study adopted a correlational research design to examine relationships among school administrative practices, organizational culture, and teachers’ service delivery in public secondary schools in Anambra State. The population comprised 6,598 teachers, from which 660 were sampled using multistage sampling. Data were collected using three validated and reliable questionnaires. A total of 618 questionnaires were returned. Pearson Product Moment Correlation, analyzed with SPSS, was used to test hypotheses at the 0.05 significance level. The results indicate a very strong positive correlation between adhocracy culture and teachers’ service delivery in public secondary schools in Anambra State. Analysis of data from a sample of teachers (N = 618) revealed a high correlation coefficient (r = 0.868), showing that increases in adhocracy culture are strongly associated with improved teachers’ service delivery. Further hypothesis testing confirmed the statistical significance of this relationship, with a p-value (0.000) lower than the accepted significance level (0.05). Consequently, the null hypothesis was rejected, establishing that adhocracy culture significantly influences teachers’ service delivery in public secondary schools in Anambra State. The study concludes that fostering adhocracy culture in public secondary schools is essential for improving teachers’ service delivery, instructional quality, and student learning outcomes in Anambra State.